Strategic Interests, Power Dynamics and Emerging Alliances in IOR - Afzal , Urooj (International Journal of Social Sciences: Current and Future Research Trends, 2020)
The Indian Ocean Region has emerged as a theatre of competition between the competing powers which are pursuing strategies to maximize their relative share of power. This region gained tremendous political, economic and strategic importance. The U.S. has embarked upon the Asia-Pacific Rebalancing strategy in its pursuit to encircle China with the help of India. This leads to realignment of strategic relations in the Indian Ocean Region, whereby India has emerged as a Major U.S. Defence Partner. This study explores how these changing relations might implicate the strategic landscape of the region. The theoretical foundation of this study would mainly revolve around the realist school of thought and a modern variant of Hans Morgenthau's realism often called as neo realism or structured realism. By using the qualitative research methodology, the study attempts to develop a balanced perspective regarding different policy objectives and foreign policy approaches of several states involved in this region including Pakistan. The Indian Ocean Region has emerged as a theatre of competition between the competing powers which are pursuing strategies to maximize their relative share of power. This region gained tremendous political, economic and strategic importance. The U.S. has embarked upon the Asia-Pacific Rebalancing strategy in its pursuit to encircle China with the help of India. This leads to realignment of strategic relations in the Indian Ocean Region, whereby India has emerged as a Major U.S. Defence Partner. This study explores how these changing relations might implicate the strategic landscape of the region. The theoretical foundation of this study would mainly revolve around the realist school of thought and a modern variant of Hans Morgenthau's realism often called as neo realism or structured realism. By using the qualitative research methodology, the study attempts to develop a balanced perspective regarding different policy objectives and foreign policy approaches of several states involved in this region including Pakistan